(untitled) - Ballon, Robert J. (New York, 1992)
Part I The labour market ; Part II The workplace ; Part III The marketplace,...
Keywords: Tập đoàn nước ngoài,Corporations, foreign; Quản lý nhân sự,Personnel management; Nhật Bản,Japan